Determinan Intellectual Capital terhadap Profitabilitas di Bank Syariah: Pengujian Mediasi Kinerja Keuangan dan Kinerja Non Keuangan - Siti Mardilia Farihah; Setiawan Setiawan (Jurnal Samudra Ekonomi dan Bisnis, 2020)
The purpose of this study is to analyze the effect of intellectual capital on financial performance and non-financial performance of Islamic banking, and its impact on the profitability of the bank. The population is 13 Sharia Commercial Banks in Indonesia. With the purposive sampling method, a sample of five Islamic commercial banks was obtained. Data analysis method in this study uses SEM PLS. The first result shows that intellectual capital has a significant negative effect on financial performance, a significant positive effect on non-financial performance, and a positive but unsignificant effect on profitability. The next results stated that financial performance and non-financial performance had a significant negative effect on profitability. The third research result states that intellectual capital has a significant positive effect on profitability through financial performance, but a significant negative effect on profitability through non-financial performance.